Study of Indicators on Acids and Bases - Kapur, Madhu (SCHOOL SCIENCE, 2017)
There is a paradigm shift in the traditional role of teachers as well as students in Constructivist Science Classroom. The teaching methods used in traditional classroom is based on objectivist view of knowledge which is grounded on the assumption that knowledge is objective, universal and complete and can be transferred from head of the teacher to the head of student. Whereas, in constructivist classroom, the role of teachers’ shift from transmitter of knowledge to facilitator of knowledge. Hence, the role of students changes from knowledge gainer to knowledge constructor. By taking this approach forward, the same concept was taught in two sections of Class VII. One was considered as the control class of 34 students, where students were taught by chalk and board method and the other one as the constructivist class, where students learnt by doing experiments themselves. In control class the students were taught about the use of indicators on acids and bases by lecture method. They were taught that the colour of an acid and a base changes when an indicator was added. This was done by drawing a table on the blackboard. The definition of an indicator was taught and the students memorised it. In the other class, the teacher was like a facilitator. The class was divided into groups and the material, i.e., an acid, a base and indicators like china rose, phenolphthalein and turmeric was given in test tubes which were distributed to the students. Here the students performed hands-on experiment and saw the change in colour of an acid and a base by using various indicators. By doing hands-on experiments students were able to relate better with the concepts given in the book as the visual impact had a far much better impression. Fussing with definition: Definition is an integral part of science, therefore, this strategy works beautifully in helping the students understand the key words involved in the definition and help them know it correctly without memorising it. The students were given key words related to the concept and they themselves came up with the definition of indicators. The students were able to evolve the definition themselves by using a constructivist strategy which is given above. When the students performed hands-on experiments the concept was understood very well and the impact was far better. The analytical data was also done which indicated that for every question asked the graph was much higher in the class where constructivist approach was used.